2011
DOI: 10.1002/clc.20981
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of β‐Blockers for Heart Rate Control in Coronary Artery Disease

Abstract: Background: Resting heart rate is an independent risk factor for cardiovascular disease and is mainly controlled by β-blockers (BBs). BBs are part of the optimal medical treatment for coronary artery disease (CAD), and their benefit correlates with resting heart rate (RHR) reduction. Hypothesis: RHR is poorly controlled in daily practice among patients with stable cardiovascular disease, and control is only achieved by some BBs. Methods: Observational, cross-sectional, and multicenter study of CAD patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…12 The different mechanisms of action of ivabradine and beta-blocker responsible for reducing heart rate mean the combination of ivabradine with low-dose bisoprolol appears to be a valuable option in patients with CABG undergoing cardiac rehabilitation. 12,30 Limitations As resting heart rate reduction may not be a class effect of beta-blockers, 9 caution should be used in interpreting our findings with the beta-blocker bisoprolol more generally. Our study examined several efficacy parameters, but data on the safety and tolerability of the combination are lacking.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…12 The different mechanisms of action of ivabradine and beta-blocker responsible for reducing heart rate mean the combination of ivabradine with low-dose bisoprolol appears to be a valuable option in patients with CABG undergoing cardiac rehabilitation. 12,30 Limitations As resting heart rate reduction may not be a class effect of beta-blockers, 9 caution should be used in interpreting our findings with the beta-blocker bisoprolol more generally. Our study examined several efficacy parameters, but data on the safety and tolerability of the combination are lacking.…”
Section: Discussionmentioning
confidence: 85%
“…As resting heart rate reduction may not be a class effect of beta-blockers, 9 caution should be used in interpreting our findings with the beta-blocker bisoprolol more generally. Our study examined several efficacy parameters, but data on the safety and tolerability of the combination are lacking.…”
Section: Limitationsmentioning
confidence: 90%
See 1 more Smart Citation
“…The effectiveness of β-blockers in controlling HR is well established. According to one report, atenolol, bisoprolol, and metoprolol were more effective than other β-blockers in managing resting HR in CHD patients 9 . Previous studies of multiple patient groups have demonstrated that changes in both 24-h average HR and resting HR were related to the dosage of β-blocker administered 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…β-blockers are among the most effective therapies for CHD. The clinical benefit and improvement in prognosis following β-blocker treatment in CHD patients have been associated with a reduction in resting HR 9 . In patients who have stable angina without contraindications, β-blocker therapy is recommended as a strategy to improve disease outcome and symptoms.…”
Section: Introductionmentioning
confidence: 99%